Purification and biochemical characterization of alkaline serine protease from caesalpinia bonducella - Khan, H.; Ali, I.; Khan, Arif-ullah; Ahmed, M.; Shah, Z.; Saeed, A.; Naz, R.; Mustafa, Mohd Rais; Abbasi, A. (Natural Products Inc, 2010)
A high molecular weight serine protease has been purified to electrophoretic homogeneity from the seeds of Caesalpinia bonducella Hem. (Caesalpiniaceae) by the combination of size exclusion and ion exchange chromatography. About 524 fold purification was achieved with an overall recovery of 6.8%. The specific activity was found to be 86 U/mg/min at pH 8.0. The calculated K(m) and V(max) were 1.66 mg/mL and 496.68 units/min per mg of protein, respectively. The molecular mass was estimated to be about 63 kDa by sodium dodecyl sulfate PAGE. The enzyme showed optimum activity at pH 8.0 and exhibited its highest activity at 40 degrees C. The enzyme was strongly inhibited by 2mM phenylmethylsulfonyl fluoride (PMSF), suggesting the presence of a serine residue at the active site. PMSF showed a pure competitive type of inhibition with the serine protease enzyme. It was observed that enzyme activity was enhanced in the presence of dications and was active against a variety of modified substrates and natural proteins.